PALEOGEOGRAPHY OF THE AZOVBLACK SEA BASIN IN QUATERNARY TIME - Yu.I. Inozemtsev; O.O. Paryshev; L.V. Stupina; E.N. Rybak (Геологія і корисні копалини Світового океану, 2019)
The article notes that during the Quaternary period there was at least 5—6 glaciations, which each time entailed a sharp change in the ecological and hydrological situation both in the Caspian Sea and in the Black Sea. The change in temperature and salinity of the waters was reflected both in the composition of the fauna and in the lithological composition of the deposited sediments. During the cooling period, the Black Sea and the Caspian Sea regressed, they were isolated from each other, as well as from the World Ocean due to the presence of the Bosphorus threshold up to a mark of –36…–37 m. During the period of global warming, the level of the World Ocean returned each time to approximately the present mark, which was also characteristic of the Black and Caspian Seas. The tendency of level fluctuations in the indicated basins was of the same type, but the rate of these fluctuations, especially at the transgression stage, had sharp differences. This is especially pronounced in the Caspian Sea, in which the level from the –13 m mark about 17 thousand years ago rose to zero, –2 m about 15,5 thousand years ago. The level of the World Ocean during this period of time rose only to the –90 m mark. The Black Sea was also in a transgressive state, but its level was determined by the height of the Bosphorus threshold. This follows from the fact that inland basins were much faster than the oceans in their filling rate. The nature of the mutual penetration of the Mediterranean and Caspian fauna into the Black Sea was determined by the state of overdeepening of the Manych Valley, the Kerch and Bosphorus Strait, which is confirmed by the presence of the Caspian fauna of the Chaudino type in the Sea of Marmara (Gallipoli), and the Mediterranean fauna (Cardium edule L.) in the East of Manych, the Northwest Caspian (ChaudoBaku time) and the Caspian Sea — In the Holocene.